Cerebrospinal fluid-contacting neurons are sensory neurons with uniform morphological and region-specific electrophysiological properties in the mouse spinal cord - Elysa Crozat; Edith Blasco; Jorge Ramirez-Franco; Priscille Riondel; Nina Jurčić; Riad Seddik; Caroline Michelle; Jérôme Trouslard; Nicolas Wanaverbecq (Communications Biology)
Abstract Cerebrospinal Fluid-contacting neurons (CSF-cNs) are GABAergic bipolar neurons found, in contact with the cerebrospinal fluid, along the vertebrate medullo-spinal central canal. They express Polycystin Kidney Disease 2-Like 1 channels (PKD2L1), members of the Transient Receptor Potential superfamily, and were shown to modulate motor activity and therefore suggested to act as a novel sensory system. However, in mice, they remain largely uncharacterized and it is crucial to comprehensively characterize their morphological and electrophysiological properties to determine whether they form a homogenous neuronal population and understand their role in the CNS. We show that CSF-cNs are distributed throughout the spinal cord with a uniform morphology and a primarily ventral localization. They exhibit region-specific properties, expression of voltage-dependent and ligand-gated conductances and detect variation in extracellular pH through activation of PKD2L1 and Acid-sensing Ion Channels. They possess GABAB and muscarinic receptors, not glutamatergic metabotropic ones, to modulate Ca2+ channels. CSF-cNs represent unique sensory neurons with a uniform morphology and electrophysiological properties that appear specific to the spinal cord segment inserted in. The future challenges in the field, will be to elucidate the physiological stimuli activating CSF-cNs and the neuronal network they are integrated in to modulate body function through specific local spinal network.